2009
DOI: 10.1002/ijc.24016
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived microparticles promote invasiveness of prostate cancer cells via upregulation of MMP‐2 production

Abstract: Prostate cancer commonly affects men in the Western world. A major factor of the life-threatening course of this disease is the high rate of metastasis, predominantly to bones. Circulating tumor cells encounter platelets and may activate them, resulting in a production of microparticles (MPs). MPs are small platelet fragments expressing membrane receptors as well as cytoplasmic constituents. Here, we report that prostate cancer cells, Clone-1 (Cl-1), preincubated with platelet-derived MPs (PMPs), demonstrate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 26 publications
3
77
2
1
Order By: Relevance
“…As detailed below (see paragraph on fibrous cap weakening), human plaque MPs harbor active proteases 116 and MPs of different cellular origin are able to induce the release of metalloproteases by different cell types. [117][118][119][120] Third, MPs regulate endothelial proliferation and capillary tube formation. Human plaque MPs isolated from endarterectomy specimens surgically obtained from patients increase endothelial cell proliferation in vitro as well as in vivo in matrigel plugs.…”
Section: Neovessel Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed below (see paragraph on fibrous cap weakening), human plaque MPs harbor active proteases 116 and MPs of different cellular origin are able to induce the release of metalloproteases by different cell types. [117][118][119][120] Third, MPs regulate endothelial proliferation and capillary tube formation. Human plaque MPs isolated from endarterectomy specimens surgically obtained from patients increase endothelial cell proliferation in vitro as well as in vivo in matrigel plugs.…”
Section: Neovessel Formationmentioning
confidence: 99%
“…Platelet-derived MPs stimulate the secretion of active MMP-2 by prostate cancer cells. 117 Furthermore, T cells and monocytes MPs induce the synthesis of MMP-1, MMP-3, MMP-9, and MMP-13 in fibroblasts. 118 Finally, T-cell-derived MPs upregulate MMP-1, MMP-3, MMP-9, and MMP-13 genes in hepatic stellate cells.…”
Section: Rautou Et Al Microparticles In Atherothrombosis 599mentioning
confidence: 99%
“…The mechanisms behind these effects are not fully understood and still under investigation. However, it has been suggested that platelet-derived microparticles might induce tumor secretion of various matrix-metalloproteinases, facilitating the metastatic process (Dashevsky et al, 2009) (Janowska-Wieczorek et al, 2005. A study on the role of platelet-derived microparticles for metastatic capacity in lung cancer revealed that there might as well be direct effects on both tumor cell proliferation and adhesion to fibrinogen and endothelial cells (JanowskaWieczorek et al, 2005).…”
Section: Platelet-derived Microparticlesmentioning
confidence: 99%
“…Many types of vesicles have been described in the literature having quite heterogeneous size, protein content, RNA content and origin. As a result there have been many names given to these different vesicle types (Table 1) (Ronquist & Brody, 1985;Ronquist & Frithz, 1986;Rooney et al, 1993;Arienti et al, 1997;Thery et al, 2006;Lehmann et al, 2008;Schiller et al, 2008;Simpson et al, 2008;Skog et al, 2008;Dashevsky et al, 2009;Di Vizio et al, 2009;Haubold et al, 2009;Jansen et al, 2009;Nilsson et al, 2009;Duijvesz et al, 2010). Unfortunately, the different names given to these vesicles lead to much confusion and it is still unclear if all of the different vesicles are unique in biological function or if they represent a sliding scale of one entity (Duijvesz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%